If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -24 = 3x + 36 Reorder the terms: -24 + 4x = 3x + 36 Reorder the terms: -24 + 4x = 36 + 3x Solving -24 + 4x = 36 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + 4x + -3x = 36 + 3x + -3x Combine like terms: 4x + -3x = 1x -24 + 1x = 36 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + 1x = 36 + 0 -24 + 1x = 36 Add '24' to each side of the equation. -24 + 24 + 1x = 36 + 24 Combine like terms: -24 + 24 = 0 0 + 1x = 36 + 24 1x = 36 + 24 Combine like terms: 36 + 24 = 60 1x = 60 Divide each side by '1'. x = 60 Simplifying x = 60
| -4fgh^2*(-2gh)= | | 6w^2+9w+2=0 | | 9=2r+r | | .33x-2=.25x+3 | | 3pq*2pr= | | 5y-11=24whatisy | | 5y-11=24wgatisy | | 2(x+1)+x=7 | | cos(36+x)+cos(x)=0 | | cosx(36+x)+cos(x)=0 | | 0.5D^2+1.5D+1=0 | | tan*x=0.625 | | 4(3x+6)=9 | | 2/x-1/7=7/x | | 10x-3=2x+1 | | sin(45)=x/18 | | x+8=x*(x-6) | | 81x^3+1=0 | | (p^-4b)/(12c^2) | | 2(3x-1)-(x-2)=5 | | (p^-4b)/12c^-2 | | 2xy-x+2y+1=0 | | 600x=8000+300x | | 600x=12000+300x | | 600x=200x+12000 | | 4x+11=38-3x | | 4x+12=20-12x | | 3x+30=45 | | (2x+4)4=8 | | -4+4x=-12x+10x | | y=-x^3+9x^2-24x+10 | | -/-18/ |